Agen Hayati yang Berperan dalam Menghambat Penyakit Hawar Daun Bakteri (HDB) yang disebabkan oleh Bakteri Xoo Pada Padi Sawah (Oryzae sativa L.) - Iwan Gunawan; Andika T. Sukma; Humairoh Humairoh; Kevin Christian B.P; Raimondo B. Saputra (xxxx-xxxx, 2020)
Gunawan I, Sukma AT, Humairoh H, Pakpahan K.CB, Saputra RB. 2020. A biological agent involved in staching bacterial leaf (HDB) caused by xoo bacteria on the rice paddies (Oryzae sativa L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xxx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One disease that is often a problem is bacterial leaf blight in rice in Indonesia. Bacterial blight caused by the bacteria Xanthomonas oryzae pv oryzae (Xoo). Symptoms that arise in the vegetative phase are called kresek and in the generative phase are called blight. This writing is done by studying the literature that is taken, analyzed, and developed into an easy-to-understand review. This study aims to determine the ability of B. subtilis, P. fluorescens, Trichoderma sp. in suppressing the development of bacterial leaf blight (HDB) caused by Xanthomonas oryzae in rice. With biological agents such as P. fluorescens, B. subtilis, and Trichoderma sp which act as antagonists to plant pathogens because they are able to produce antibiotics, siderophores and volatile substances. Based on a study of the literature, that the biological agent sp is used to control bacterial leaf blight in rice because it can induce resistance in controlling a disease in rice varieties infected with Xanthomonas oryzae. The conclusion drawn in this literature review is that biological agents are effective in controlling leaf blight.